THE ROLE OF SOCIAL MEDIA IN THE PROCESS OF INFORMING THE PUBLIC ABOUT DISASTER RISKS - Cvetković, Vladimir M; Nikolić, Aleksandra; Ivanov, Aleksandar (Journal of Liberty and International Affairs (Bitola), 2023)
Social media informs the public about the most important events and conveys important information. Before, during, and after disasters, social media are used to disseminate information about disasters and collect data relevant to the implementation of preparedness, response, and recovery activities and measures. Social networks are effective in disseminating information and warnings, as well as in educating the public. The subject of the research is examining the influence of demographic factors on the effectiveness of social media in informing the public about the risks of disasters. Using an online survey questionnaire and according to the snowball principle, a survey of 247 respondents was conducted in 2022. The research results show no statistically significant relationship between the respondents’ education level and the assessment of the effectiveness of social media reporting on disasters. Using social media can improve communication between stakeholders in disaster management and facilitate coordination of efforts, fostering communication and allocation of resources. To effectively use social media in disaster management, decision-makers in the disaster management system must be aware of new technologies, their disadvantages and advantages, and ways to collect and analyze data from social networks.